Increase Working Efficiency by Using the Newly Created Polymer Composite Material in Pneumatic Transport - Toychiyev Khasanboy Tokhir ugli; Toychiyev Khusanboy Tokhir ugli; Bakirov Lutfillo Yuldoshaliyevich (Genius Journals, 2023)
Today, it is important to improve the modern machine-building industry, to create improved devices of technologies, machines, and mechanisms that meet modern requirements, to create competitive and import substitutes for various fields of production, to conduct in-depth fundamental research, and to solve current scientific and technical issues. Also, the purposeful use of high-performance composite polymer materials to ensure the operational reliability of cotton processing machines, and the reduction of the negative impact of the working surfaces of technological equipment on cotton surfaces through the use of new materials is one of the urgent scientific and technical problems waiting to be solved.
Keywords: thermoprotective polymer; pneumotransport; fan blade